2010
DOI: 10.1038/nmat2854
|View full text |Cite
|
Sign up to set email alerts
|

Fractal avalanche ruptures in biological membranes

Abstract: Bilayer membranes envelope cells as well as organelles, and constitute the most ubiquitous biological material found in all branches of the phylogenetic tree. Cell membrane rupture is an important biological process, and substantial rupture rates are found in skeletal and cardiac muscle cells under a mechanical load. Rupture can also be induced by processes such as cell death, and active cell membrane repair mechanisms are essential to preserve cell integrity. Pore formation in cell membranes is also at the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(87 citation statements)
references
References 24 publications
4
81
2
Order By: Relevance
“…We note that the rupture patterns we observe (Fig. 5A, lower row) are similar to the floral instability patterns seen in rupturing multilamellar vesicles (41).…”
Section: Resultssupporting
confidence: 83%
“…We note that the rupture patterns we observe (Fig. 5A, lower row) are similar to the floral instability patterns seen in rupturing multilamellar vesicles (41).…”
Section: Resultssupporting
confidence: 83%
“…Lipid film precursors, buffered solutions, and high energy surfaces were prepared as described earlier[1]. As shown in Fig 1, Multilamellar (or onion shell) lipid vesicles were manually deposited on a silicon oxide surface, where self-spreading occurred spontaneously, forming a circular double bilayer patch (Fig 1A) with a fixed proximal (lower) and mobile distal (upper) bilayer (Fig 1B).…”
Section: Methodsmentioning
confidence: 99%
“…It was recently shown that a double phospholipid bilayer membrane, forming spontaneously from a lipid source on a solid support, can form both floral and fractal ruptures[1]. In double bilayer membranes, the two individual stacked bilayers are in close proximity, separated by a nanoscopically thin water layer.…”
Section: Introductionmentioning
confidence: 99%
“…Lipid films on a hydrophilic substrate in water correspond to the so-called symmetric wetting situation [16,17], where the number of monolayer leaflets in the supported film is even, due to the preferential affinity of both the solid and the liquid with the polar head of the molecules. In this case, spreading has been described as the rolling of the front bilayer creeping on the solid surface [18][19][20][21]. The same mechanism does not transpose to the asymmetric wetting situation [16,[22][23][24], where the solid and the free surface prefer to be in contact with opposite parts of the molecule (hydrophilic versus hydrophobic).…”
mentioning
confidence: 99%